Decision-making during problem-solving and innovation in an urban dwelling population of yellow mongooses (Cynictis penicillata) - Dabhelia, Muneera (My University, 2022)
The rapid exponential growth of towns and cities has impacted wildlife in various ways, causing the decline and redistribution of species. Yet, some wild animal species have established themselves in urban environments through behavioural modifications. Urban adapted animals are presumed to have advanced cognitive abilities and are behaviourally flexible in terms of their decision-making processes when faced with a novel problem. Decision-making in urban animals has not been extensively. I studied decision-making in two populations urban of yellow mongooses (Cynictis penicillata) using a problem-solving task that increased in complexity. The behaviours of the mongoose while interacting with a novel object was analysed using three levels of interpretation. The mongooses were studied in areas of varying human disturbance (a Nature Estate where wildlife was located away from human residents and an Eco Estate where mongooses had regular close contact with people), south of Johannesburg, South Africa. I used a single-access puzzle box with a hinged lid, containing a food incentive to record the general behaviour and decision making of the yellow mongooses to open the box and gain access to the food incentive. The experiment comprised of four stages in sequential order on different days, starting with an open puzzle box with food (stage 1), to a closed box propped open with a stick (stage 2), to a closed box (stage 3), and finally a closed box with an impediment on the lid (stage 4). Ten sites (1 mongoose per site) were sampled repeatedly for several trials (5 to 9) for each stage. From camera trap footage, I assessed how long it took the mongooses to open the box (latency of completion) in each stage of complexity, the frequency of behaviours, how often each behaviour followed another (behavioural transitions) while the mongooses were interacting with the puzzle box and the spontaneous alternation behaviour score (SAB score) to analysis the moment-to-moment change in behaviours. The latency to consume the food incentive was lowest in stage 1, increased in subsequent stages and was faster in the Eco Estate compared to the Nature Estate. Eight behaviours were recorded: biting, sniffing, pawing, pulling, pushing the puzzle box, digging around or underneath the box, locomotion around the puzzle box, and vigilance. The frequency of three behaviours - digging, investigating and vigilance was summed – to account for the small sample sizes. The frequency of digging and the frequency of vigilance was lowest in stage 1 compared to subsequent stages. The frequency of investigating was highest in stages 1 and 2 and decreased in stages 3 and 4. Location did not significantly predict the frequency of digging, although the frequency of investigating and vigilance was higher in the Eco Estate compared to the Nature Estate. For the behavioural 3 transitions and SAB scores, all eight behaviours were analysed. The number of significant behavioural transitions increased as the level of complexity of the task increased. The number of significant transitions in stage 2 and stage 3 in the Eco Estate was greater compared to the Nature Estate, but in stage 4 the number of significant transitions was greater in the Nature Estate compared to the Eco Estate. The SAB score for stage 2 did not significantly differ from stage 3. However, the SAB score for stage 3 were significantly lower compared to those of stage 4. The SAB score in the Eco Estate was significantly higher than the Nature Estate. My findings indicate that the yellow mongooses were able to modify their decision-making strategies by selecting behaviours that were most appropriate to solving the problem and rejecting ones that did not, particularly at greater stages of complexity of the task. In addition, mongooses in the Eco Estate, where they encounter people more often, made less accurate moment to moment decisions and took longer to solve the puzzle box tasks compared to the mongooses in the Nature Estate. Such flexibility in decision-making likely enables the yellow mongooses to thrive in human-impacted environments.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Animals, Plants and Environmental Sciences, University of the Witwatersrand, Johannesburg, 2022